PERBEDAAN PERTUMBUHAN DAN PERKEMBANGANBAHASA BERDASARKAN LENGKAP TIDAKNYA STATUSORANG TUANYA DI KECAMATAN KARTASURA - NUGRAHA, SENDY ADITYA (2010)
SENDY ADITYA NUGRAHA, J 500 060 060, 2010. Skripsi. The Differentials Of Growth and Development Of Language According To The Completely Of Parental Status In District Of Kartasura Growth is a process increasing of bodies, organs, and tissue from conception to the maturity in teen. Development is a process which increasing of skills in a structure and function that correlate with change of quality and quantity. Child means group of people under five years old includes of neonates 0 years until five years old (4 years, 11 months, 29 days). In general uses terms 0-4 years notation. Family is the first of environment who support of growth and development of child. Child period knowns golden age, which growth and development is important. Parents as members of family have many functions and task to support of child growth and development. This research was conducted to know the differentials of growth and language development in complete and uncomplete family. This research uses analytic observasional with cross sectional approximations. Data was got from interviews to each respondens. Before an interview, respondens get an inform consent to sign. Measurement of growth was got from nutritional status with anthropometry (Weight/Age) and then compare with standart of WHO 2005. Language development was got from Denver II test. Statistic result of language development shows that p = 0,025, it mean significant because p < 0,05. Statistic of Nutritional Status shows that p = 0,487, it mean no significant because p > 0,05. This research concludes that it has significant differentials language development of child between complete and uncomplete of parental status. There is no differentials growth of child between complete and uncomplete of parental status.